Hydrochemical Characteristics and Formation Mechanism of Strontium-Rich Groundwater in Shijiazhuang, North China Plain. (25th March 2021) - Li, Duo; Gan, Shuang; Li, Junfeng; Dong, Zihan; Long, Qi; Qiu, Shuwei; Zhou, Yahong; Lu, Changyu
Abstract : Strontium is a kind of trace element. Groundwater containing strontium is called mineral water when its content reaches a level that is beneficial for human physiology. Some groundwater resources in Shijiazhuang are rich in strontium. In this study, groundwater samples collected from 103 sites were studied for the hydrochemical characteristics of strontium and its formation mechanism in the groundwater system in Shijiazhuang City. The methods of source provenance analysis, factor correlation analysis, and runoff condition analysis were carried out in the study. The results showed that the content of strontium in eastern Shijiazhuang is higher than 0.229 mg/L, with a maximum content of 1.942 mg/L. The source of strontium is the dissolution of strontium-containing minerals in carbonate rock, sheet hemp rock, clastic rock, and granite in the Taihang Mountain area of the Hutuo River Basin. Strontium is positively correlated with total dissolved solids, bicarbonate, calcium magnesium, and free carbon dioxide. The erosion ability of groundwater strengthens the dissolution of strontium, and the geochemical action is mainly due to the dissolution. The enrichment and distribution of strontium are related to the conditions of groundwater runoff. Areas with good runoff conditions and strong mining are low in strontium, while areas with poor runoff conditions have high strontium content.